The Use of Full-Grained, Fragmented, and Reduced Marine Yeast Powder in Fodder Formulation to Improve the Growth of Eel Fish (Anguilla bicolor) - Manik, Ria Retno Dewi Sartika; Ekawati, Arning Wilujeng; Hardoko, Hardoko (The Journal of Experimental Life Science, 2016)
Ikan Sidat or eel fish (Anguilla bicolor) is a popular fish commodity in domestic trade as well as for export commodity. The use of marine yeast as fodder suffers from some weaknesses since it contains nucleic acids and rigid thick cell walls that obstruct the absorbance of nutrition. Optimizing the use of marine yeast as fodder ingredients can be done by fragmenting and reducing the yeast. This research attempts at optimizing the use of marine yeast regarding its rate of growth, fodder efficiency and the survival rate of eel fish. This research employs the complete random design using 4 different treatments and 3 repetition. In the four treatments, the fodder contained protein (45%) and iso energy (3.600 kkal.kg-1 fodder), which were applied to the treatment A 0% (control), B 5% (complete), C 5% (fragmented) and D 5% (reduced). The parameters used in this study were survival rate, specific growth rate, ratio of fodder conversion, ratio of protein efficiency, energy retention, protein retention and rate of metabolism. The data of this study showed the best result in the treatment D, 5% (reduced), showing survival rate value of 95.56%, specific growth at 1.12, food conversion ratio of 2.27, protein efficiency ratio of 0.98, protein retention at 18.26%, energy retention of 16.57, and protein metabolism rate at 81.96%. Keywords: eel fish, growth, marine yeast.